2013
DOI: 10.1021/ci400178h
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling Study of Dihydrofolate Reductase Inhibitors. Molecular Dynamics Simulations, Quantum Mechanical Calculations, and Experimental Corroboration

Abstract: A molecular modeling study on dihydrofolate reductase (DHFR) inhibitors was carried out. By combining molecular dynamics simulations with semiempirical (PM6), ab initio, and density functional theory (DFT) calculations, a simple and generally applicable procedure to evaluate the binding energies of DHFR inhibitors interacting with the human enzyme is reported here, providing a clear picture of the binding interactions of these ligands from both structural and energetic viewpoints. A reduced model for the bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 86 publications
5
61
0
Order By: Relevance
“…We recently reported that the charge density value at the bond critical point (ρ(r b )), which is a descriptor of the strength of the different bonds, can be used to quantify the affinity of a ligand to form a complex ligand-receptor [67,70]. We have analyzed the complexes obtained for the three compounds reported here 2 , 3 and 4 using this type of analysis and also included compound PF543 for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported that the charge density value at the bond critical point (ρ(r b )), which is a descriptor of the strength of the different bonds, can be used to quantify the affinity of a ligand to form a complex ligand-receptor [67,70]. We have analyzed the complexes obtained for the three compounds reported here 2 , 3 and 4 using this type of analysis and also included compound PF543 for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…MD trajectories were projected along the first PC (PC1) and frames with extreme values of projection were selected for subsequent charge density topological analysis using QTAIM . This analysis has been very useful for evaluating the interactions in bio‐molecular systems …”
Section: Computational Detailsmentioning
confidence: 99%
“…[1][2][3] Baquiloprim (BQP), trimethoprim (TMP), ormetoprim (OMP) and diaveridine (DVD) have been used in human and veterinary medicines for the treatment and prevention of disease since many years. [1][2][3] Baquiloprim (BQP), trimethoprim (TMP), ormetoprim (OMP) and diaveridine (DVD) have been used in human and veterinary medicines for the treatment and prevention of disease since many years.…”
Section: Introductionmentioning
confidence: 99%